Co-delivery of sorafenib and metformin from amphiphilic polypeptide-based micelles for colon cancer treatment - Zhang, Xiaohui; Cao, Lanqing; Xu, Guangmeng; He, Hongyu; Zhao, Hongyu; Liu, Tongjun (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is a common clinical disease with a poor prognosis and a high recurrence rate. Chemotherapy is important to inhibit the post-surgical recurrence of CRC patients. But many limitations restrict the further application of chemotherapy. In this study, sorafenib (Sor) and metformin (Met) co-loaded poly(ethylene glycol)-block-poly(L-glutamic acid-co-L-phenylalanine) [mPEG-b-P(Glu-co-Phe)] micelles were developed. The characterizations, drug release, in vivo biodistribution, and pharmacokinetics of the micelles were analyzed. The treatment efficacy of the dual-drug loaded micelles was evaluated in a subcutaneous colon cancer mice model. Sor is a common molecular target agent that can inhibit the mitogen-activated protein kinase (MAPK) pathway to treat solid tumors. Met can also regulate the MAPK pathway and inhibit the expression of the phosphorylated extracellular signal-regulated kinase (p-ERK). Moreover, both Sor and Met play important roles in cell cycle arrest. The integration of these two drugs aims to achieve synergistic effects against colon cancer. The micelles can be targeted to cancer cells and possess longer blood circulation time. The two agents can be released rapidly in the tumor sites. The in vivo study showed that the micelles can prevent tumor progression by inhibiting the expressions of p-ERK and cyclin D1. This study indicated that the Sor/Met-loaded micelles are suitable for CRC treatment.